2023
DOI: 10.1038/s41598-023-33196-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Charlson Comorbidity Index on surgical complications and reoperations following simultaneous bilateral total knee arthroplasty

Abstract: Simultaneous bilateral total knee arthroplasty (TKA) might be associated with higher postoperative morbidity and mortality rates compared with staged bilateral TKA. However, risk factors for surgical complications and reoperations following simultaneous bilateral TKA remain elusive. We conducted this retrospective, single-surgeon case series from 2010 through 2019. A total of 1561 patients who underwent simultaneous bilateral TKA procedures were included. The outcome domains included 30-day and 90-day readmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…An underutilized resource may be an urgent care, which aids in triaging lower acuity patients between the clinic and the hospital [ 18 ]. Our investigation showed that robotic arthroplasty is associated with an increased rate of patients with a postoperative phone call compared to manually performed arthroplasty [ 7 , 14 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…An underutilized resource may be an urgent care, which aids in triaging lower acuity patients between the clinic and the hospital [ 18 ]. Our investigation showed that robotic arthroplasty is associated with an increased rate of patients with a postoperative phone call compared to manually performed arthroplasty [ 7 , 14 , 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%